An Example of Using Collaborative Online International Learning for Petroleum and Chemical Engineering Undergraduate Courses - Durand, Helen; Balhasan, Saad (International Review of Research in Open and Distributed Learning, 2023)
This work describes an international collaboration experience carried out between our process design and petroleum property evaluation courses. This collaboration was developed as part of a partnership between the American University of Ras Al Khaimah (AURAK) in Ras Al Khaimah, United Arab Emirates, and Wayne State University in Detroit, Michigan, United States of America, using a program called Collaborative Online International Learning (COIL) from the State University of New York (SUNY) system. The COIL program provides training to faculty on engaging students in international and cross-disciplinary projects to promote skills needed in the current work force. The COIL training meetings facilitated pairing faculty of different disciplines in different parts of the world and provided a structure for developing a collaborative project. The collaborative project that we undertook in fall 2021, and which we detail throughout this article, was titled Upstream and Downstream of Petroleum Economics.